The Himalaya-Bengal Fan Denudation-Accumulation System during the Past 20 Ma - G. Einsele; L. Ratschbacher; A. Wertzel (Berita Sedimentologi, 1998)
Mass balances for both denudation in the Himalayas and sediment accumulation in the Subhimalayan basins, including the Bengal deep-sea fan but excluding the Indus fan, yield 7.1 x 10^6 km2 and 7.4 x 10^6 km2 (s +/- 20%), rock of 2.75 g/cm3 density, respectively, for the past 20 Ma. Coarsening and increased sediment accumulation rates in the foreland basin and in the Bengal foredeep indicate accentuated tectonic activity and unroofing in the Himalayas since that time. The sediment volume includes ≥ 1 x 10^6 km3 of Neogene Bengal fan sediment that was lost via the Nicobar fan to the Sunda accretionary wedge. In addition, the Indian peninsular rivers contributed about c. 0.6 x 10^6 km3 of solid load to the basins. Average denudation during the past 20 Ma, as derived from geothermobarometric data and restored cross sections, occurred most rapidly along the High Himalayan crystalline chain (vertical unroofing, c. 1000 m/Ma; northward lateral retreat of southern Himalayan slope, exposed to monsoonal rain, ≥ 3.5 km/Ma), and much slower in the Tehtyan sedimentary zones to the north (average 150 m/Ma). The solute loads of the modern Himalayan rivers indicate a mean chemical denudation rate of 17 m/Ma. The distinct decrease in sediment accumulation on the outer Bengal fan between about 7 and 1 Ma (in contrast to the Indus fan) is probably caused by exogenic factors rather than by a significant decline in tectonic activity. Pre-20 Ma sediments in the Subhimalayan basins were derived mainly from the southern margin of the Tibet plateau or form sources outside the study area.